2016
DOI: 10.1039/c5ra25220b
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole-based ratiometric fluorescent probe for the sensitive and selective detection of cysteine over homocysteine and glutathione in living cells

Abstract: A new fluorescent probe (DPP-AC) based on diketopyrrolopyrrole with an acrylate group was designed and synthesized for the sensitive and selective detection of biological thiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Diketopyrrolopyrrole (DPP) and their derivatives have attracted considerable research interests over the last few decades due to their relatively simple synthesis, intense color and excellent photo-stability. Currently, DPPs have been extensively applied in construction of materials for twophoton absorption [23,24], fluorescent probes [25][26][27] and imaging [28,29]. DPP derivatives functionalized with electron donor groups usually exhibit red to near-infrared (NIR) emission and large Stokes shifts that are advantageous in biological applications [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Diketopyrrolopyrrole (DPP) and their derivatives have attracted considerable research interests over the last few decades due to their relatively simple synthesis, intense color and excellent photo-stability. Currently, DPPs have been extensively applied in construction of materials for twophoton absorption [23,24], fluorescent probes [25][26][27] and imaging [28,29]. DPP derivatives functionalized with electron donor groups usually exhibit red to near-infrared (NIR) emission and large Stokes shifts that are advantageous in biological applications [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that, in contrast to Cys, these other biothiols could not effectively participate in the intramolecular cyclization and hence not initiate the subsequent disassembly of the probe to release AF under ambient test conditions. The results were consistent with earlier findings of acrylate-based fluorescent indicators showing selective detection of Cys over other biothiols. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The common amino acids and biothiols do not make any significant alteration in the response current of Cys; these analytical results were in agreement with the Cys-selective fluorescent indicators. 27,28 Thus, the results showed the designed probe to have excellent selectivity for Cys over other biothiols and over large amounts of other potentially interfering species. Further, the interaction of the probe with active sulfur species such as NaHS, Na 2 S, Na 2 S 2 O 3 , and polysulfides (S 2 2− , S 3 2− , and S 4 2− ) were analyzed in the presence and absence of Cys.…”
Section: Nmr and Esi Mass Spectroscopies (Figures S6− S9)mentioning
confidence: 86%
See 2 more Smart Citations